(Un)romantic Becomings: Girls, Sexuality-assemblages, and the School Ball. Issue 2 (1st June 2022) - Ingram, Toni
Abstract: Popular culture and media often portray school balls and proms as romantic spaces and having a date is perceived as the norm. While gender(ed) and heterosexual discourses continue to shape young people's experiences, girls' understandings of the school ball do not necessarily conform to dominant ideas. In this article, I draw on a new materialist ontology of sexuality to explore the relations in-between girls, dates, and the school ball. I examine ball-girl-date encounters as sexuality-assemblages comprising bodies, spatial-material arrangements, practices, and imaginings. In this frame, sexuality is conceptualized as becoming via an array of material-discursive, human, and more-than-human forces. I consider how ball-girl capacities and desires become emergent and contingent, opening up ways of thinking about girls and the school ball beyond popular cultural constructions.